A Systematic Review Assessing Medical Treatment for Rectovaginal and Enterovesical Fistulae in Crohn's Disease. Issue 9 (October 2016) - Kaimakliotis, Pavlos; Simillis, Constantinos; Harbord, Marcus; Kontovounisios, Christos; Rasheed, Shahnawaz; Tekkis, Paris P.
Abstract : Background: Rectovaginal and enterovesical fistulae are difficult to treat in patients with Crohn's disease. Currently, there is no consensus regarding their appropriate management. Aim of the Study: The aim of the study was to review the literature on the medical management of rectovaginal and enterovesical fistulae in Crohn's disease and to assess their response to treatment. Method: A literature search of MEDLINE, EMBASE, Science Citation Index Expanded, and Cochrane was performed. Results: Twenty-three studies were identified, reporting on 137 rectovaginal and 44 enterovesical fistulae. The overall response rates of rectovaginal fistulae to medical therapy were: 38.3% complete response (fistula closure), 22.3% partial response, and 39.4% no response. For enterovesical fistulae the response rates to medical therapy were: 65.9% complete response, 20.5% partial response, and 13.6% no response. Specifically, response to anti-tumor necrosis factor therapy of 78 rectovaginal fistulae was: 41.0% complete response, 21.8% partial response, and 37.2% no response. Response of 14 enterovesical fistulae to anti-tumor necrosis factor therapy was: 57.1% complete response, 35.7% partial response, and 7.1% no response. The response to a combination of medical and surgical therapy in 43 rectovaginal fistulae was: 44.2% complete response, 20.9% partial response, and 34.9% no response. Conclusions: Medical therapy, alone or in combination with surgery, appears to benefit some patients with rectovaginal or enterovesical fistula. However, given the small size and low quality of the published studies, it is still difficult to draw conclusions regarding treatment. Larger, better quality studies are required to assess response to medical treatment and evaluate indications for surgery. Abstract : Supplemental Digital Content is available in the text.